2002
DOI: 10.4049/jimmunol.169.7.3652
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Recognition Via Toll-Like Receptor-Dependent and -Independent Pathways Determines the Cytokine Response of Murine Dendritic Cell Subsets to CD40 Triggering

Abstract: Dendritic cells (DC) can produce Th-polarizing cytokines and direct the class of the adaptive immune response. Microbial stimuli, cytokines, chemokines, and T cell-derived signals all have been shown to trigger cytokine synthesis by DC, but it remains unclear whether these signals are functionally equivalent and whether they determine the nature of the cytokine produced or simply initiate a preprogrammed pattern of cytokine production, which may be DC subtype specific. Here, we demonstrate that microbial and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
176
3
3

Year Published

2003
2003
2008
2008

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 204 publications
(191 citation statements)
references
References 51 publications
9
176
3
3
Order By: Relevance
“…Furthermore, higher production of IL-6 was observed by CD8 -DC compared to CD8 + DC (97 vs. 19 pg/mL). These results are in line with previous reports [41][42][43], and indicate restricted cytokine production by CD8 -DC after recognition of yeast.…”
Section: Presentation Of Yeast Antigens By Cd8 + and Cd8 -Dc Subsetssupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, higher production of IL-6 was observed by CD8 -DC compared to CD8 + DC (97 vs. 19 pg/mL). These results are in line with previous reports [41][42][43], and indicate restricted cytokine production by CD8 -DC after recognition of yeast.…”
Section: Presentation Of Yeast Antigens By Cd8 + and Cd8 -Dc Subsetssupporting
confidence: 93%
“…Furthermore, higher production of IL-6 was observed by CD8 -DC compared to CD8 + DC (97 vs. 19 pg/mL). These results are in line with previous reports [41][42][43], and indicate restricted cytokine production by CD8 -DC after recognition of yeast. Fungal stimulation of DC has been reported to lead to IL-23 production and subsequent activation of Th17 cells [42,44].…”
supporting
confidence: 93%
“…It is becoming increasingly clear that not all aspects of DC activation are regulated concordantly and that they can be differentially induced by innate vs adaptive signals. For example, innate stimuli can promote production of cytokines such as IL-12, IL-10, or IFN-␣ whereas CD40 ligation cannot initiate cytokine synthesis but can amplify that which has been initiated by microbial signals (14,15). However, it is not clear whether other aspects of DC activation are similarly dependent on microbial priming and whether T cell-derived signals act exclusively on Ag-bearing DC or also regulate the function of bystander cells.…”
mentioning
confidence: 95%
“…It has previously been shown that TLRs mediate translation of microbial recognition into expression of specific subsets of chemokines and cytokines by macrophages and dendritic cells (6,21,53,54). Furthermore, TLR2 and TLR4 have been shown to induce different sets of chemokines and cytokines, implying that the innate immune response can be customized for different pathogens (11,15,39). Recent evidence has shown that C. pneumoniae activates the innate immune system via TLRs.…”
Section: Discussionmentioning
confidence: 99%